2023
DOI: 10.3389/fmicb.2023.1167923
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the characteristic skin microorganisms in different grades of acne and different acne sites

Abstract: BackgroundThe increasing maturity of sequencing technology provides a convenient approach to studying the role of skin microorganisms in acne pathogenesis. However, there are still too few studies about the skin microbiota of Asian acne patients, especially a lack of detailed analysis of the characteristics of the skin microbiota in the different acne sites.MethodsIn this study, a total of 34 college students were recruited and divided into the health, mild acne, and severe acne groups. The bacterial and funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…1,4,6,16,18 There is no consensus on the characteristics of the acneassociated microbiome, with differences between studies likely being due to the influence of the body site analysed, sebum levels, puberty stage, acne severity and inflammatory levels, as well as sampling methods (skin surface or comedones) and other analytical parameters. 6,7,14,18 However, similar to our findings in early stage acne, reduced alpha diversity of the bacterial community has been previously documented in acne subjects compared to non-acne subjects. 10,28,29 In these studies, the decrease in bacterial diversity was shown to be associated with late puberty, inflammatory lesions, higher acne severity grades and/or epidermal barrier impairment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1,4,6,16,18 There is no consensus on the characteristics of the acneassociated microbiome, with differences between studies likely being due to the influence of the body site analysed, sebum levels, puberty stage, acne severity and inflammatory levels, as well as sampling methods (skin surface or comedones) and other analytical parameters. 6,7,14,18 However, similar to our findings in early stage acne, reduced alpha diversity of the bacterial community has been previously documented in acne subjects compared to non-acne subjects. 10,28,29 In these studies, the decrease in bacterial diversity was shown to be associated with late puberty, inflammatory lesions, higher acne severity grades and/or epidermal barrier impairment.…”
Section: Discussionsupporting
confidence: 90%
“…Studies investigating the genomic composition of the skin microbiome have identified differential microbiota profiles between skin samples from acne-prone subjects and non-acne subjects, as well as across acne grades and skin sites. 6,[13][14][15] Other clinical studies have also identified specific microbiome profiles in preadolescents with developing acne, likely due to hormone-driven increases in sebum levels. 10,16,17 Acne lesions are typically characterized by the dominance of specific pathogenic phylotypes of C. acnes and an elevated abundance of Staphylococci.…”
mentioning
confidence: 99%
“…On the other hand, the taxonomic profile results closely resemble those obtained by Guo 37 in a study of the skin microbiome in different grades of acne using 16S and 18S rRNA gene sequencing. The study showed that Cutibacterium (formerly Propinobacterium ) is present in healthy skin as normal commensal, but when the skin becomes unbalanced due to an alteration such as acne, there is a growth of Cutibacterium that correlates with acne severity.…”
Section: Discussionsupporting
confidence: 79%
“…The distribution of Cutibacterium in mild acne and in healthy skin in the samples of Guo's study was very similar to the respective distribution of Cutibacterium before and after treatment in the samples from the present study. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Guo et al did not detect differences in species diversity between healthy individuals and those with mild or severe acne in a total of 34 college students in China. In that study, 16S and 18S rRNA gene sequencing was used to investigate Propionibacterium , Staphylococcus , Corynebacterium , and Malassezia genera [ 33 ]. Studies in Japanese patients have reported the phylotype IA2 as strongly acne-associated, suggesting geographic differences between Europe and Asia [ 34 , 35 ].…”
Section: Cutibacterium Acnes In Acne Pathogenesismentioning
confidence: 99%